2022
DOI: 10.1016/j.immuni.2021.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic adaptation of lymphocytes in immunity and disease

Abstract: Adaptive immune responses mediated by T cells and B cells are crucial for protective immunity against pathogens and tumors. Differentiation and function of immune cells require dynamic reprogramming of cellular metabolism. Metabolic inputs, pathways, and enzymes display remarkable flexibility and heterogeneity, especially in vivo. How metabolic plasticity and adaptation dictate functional specialization of immune cells is fundamental to our understanding and therapeutic modulation of the immune system. Extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(89 citation statements)
references
References 230 publications
(311 reference statements)
2
67
0
Order By: Relevance
“…In addition to direct effects on metabolic pathways, proteomics experiments revealed that IL2 also affected the metabolism of in vitro-derived effector CTLs by controlling expression of nutrient transporters and other environmental sensors (122). Given that metabolic shifts during T cell activation are strongly associated with differentiation outcomes (123), these data suggest a mechanism by which differences in the local cytokine and costimulatory environment during activation might propagate through divergent differentiation fates.…”
Section: Interplay Of Environment With Response Heterogeneitymentioning
confidence: 95%
“…In addition to direct effects on metabolic pathways, proteomics experiments revealed that IL2 also affected the metabolism of in vitro-derived effector CTLs by controlling expression of nutrient transporters and other environmental sensors (122). Given that metabolic shifts during T cell activation are strongly associated with differentiation outcomes (123), these data suggest a mechanism by which differences in the local cytokine and costimulatory environment during activation might propagate through divergent differentiation fates.…”
Section: Interplay Of Environment With Response Heterogeneitymentioning
confidence: 95%
“…Central to host defense are CD8 + T cells, which are critical for pathogen clearance and protecting the host from re-infection through long-lived immune memory ( 1, 2 ). One of the fundamental biological programs supporting T cell effector function is cellular metabolism, which generates energy and biosynthetic precursors essential for CD8 + T effector (Teff) cell proliferation, survival, and production of effector molecules (i.e., IFN-Îł, TNF-α, and cytolytic factors) ( 3–5 ). CD8 + Teff cells undergo extensive metabolic rewiring to arm themselves with the bioenergetic and biosynthetic capacity to successfully protect the host ( 6, 7 ).…”
Section: Main Textmentioning
confidence: 99%
“…2a ). CD8 + T cells display plasticity in metabolic fuel choice, which allows them to operate and maintain effector function in diverse metabolic environments ( 5 ). To compare the contribution of KB-derived carbon with other carbon sources for TCA cycle metabolism, we cultured CD8 + Teff cells in the presence of 13 C-labelled substrates at concentrations commonly observed in plasma ( 38, 39 ) and assessed contribution to TCA cycle-derived metabolites.…”
Section: Main Textmentioning
confidence: 99%
“…Upon engagement of the T cell receptor (TCR) and costimulatory receptors, CD4 + T H cells escalate their metabolism to support clonal expansion and energetically demanding effector functions ( 1 ). Nutrient uptake and protein and lipid synthesis are massively induced, and energy production is both augmented and diversified ( 2 , 3 ). Effector T cells (T eff ) get much of their energy from oxidative phosphorylation (OxPhos), a process aided by increased mitochondrial mass and enhanced mitochondria function after activation ( 4 ).…”
Section: Introductionmentioning
confidence: 99%